Metformin [Working Title] 2020
DOI: 10.5772/intechopen.91148
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Metformin Mechanism of Action and Clinical Application

Abstract: Metformin is the first-line medication for Type 2 diabetes (T2D) treatment, and it is the only US FDA approved oral antidiabetic medication for pediatric patients with T2D 10 years and older. Metformin is also used to treat polycystic ovary syndrome (PCOS), another condition with underlying insulin resistance. The clinical applications of metformin are continuing to expand into other fields including cancer, aging, cardiovascular diseases, and neurodegenerative diseases. Metformin modulates multiple biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 167 publications
0
11
0
Order By: Relevance
“…Metformin is a widely prescribed insulin-sensitizing agent in current clinical use. Despite being most commonly associated with its ability to decrease plasma glucose levels, the knowledge about its novel properties and effects continues to evolve [31]. Its action modulates multiple biological pathways.…”
Section: The Effect Of Metformin Treatment On Insulin Resistance and ...mentioning
confidence: 99%
“…Metformin is a widely prescribed insulin-sensitizing agent in current clinical use. Despite being most commonly associated with its ability to decrease plasma glucose levels, the knowledge about its novel properties and effects continues to evolve [31]. Its action modulates multiple biological pathways.…”
Section: The Effect Of Metformin Treatment On Insulin Resistance and ...mentioning
confidence: 99%
“…Metformin has been found to have other beneficial properties in recent years, including the cardiovascular protective effect (Dore et al, 2018;Loi et al, 2019) and increasing insulin sensitivity have been identified for metformin in the past years as it is used for the treatment of polycystic ovary syndrome (PCOS) (Costello et al, 2019;Morley et al, 2017), prediabetes, gestational diabetes mellitus (GDM) and even for management overweight and obesity, currently (Castro-Martínez et al, 2014;Kitabchi et al, 2005). Metformin also reduces mortality due to diseases such as diabetes, cancer, and cardiovascular disease as a result of its anti-aging properties (Glossmann and Lutz, 2019;Soukas et al, 2019;Yan et al, 2020). Increasing lifespan in the animal models and humans (Anisimov et al, 2008(Anisimov et al, , 2011Glossmann and Lutz, 2019) is among other recognized properties of metformin.…”
Section: Introductionmentioning
confidence: 99%
“…Although, metformin promises as an anti-cancer agent [49,52], its mechanism of action in cancer of different origins is yet to be fully understood and whether it will be a potential therapy for metastasis-the leading cause of deaths in cancer [52,53]. Studies reported metformin had anticancer effect dependent or independent of AMPK activation [48,53]. AMPK activation was reported in various contexts to be involved in the modulation of stress and unfolded protein response (UPR) [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…More so, metformin downregulated the expression of two highly expressed proteasome genes (PSMB2 and PSMD3) and abrogated antioxidant genes in ECM detached cells. Metformin modulates energy metabolism to induce its therapeutic effect in various disease conditions [53]. The observed reduction in ATP generated due to inhibition of complex I /OXPHOS fosters increased ROS generation and activation of AMPK in metformin-treated cells suggesting impaired mitochondrial metabolic function.…”
Section: Discussionmentioning
confidence: 99%